Internalisation Of Constructivism Theory In Islamic Religious Education Learning - Muhammad Azamuddin Syahapala; Mohammad Nur Zein; Nurani (Jurnal Hadratul Madaniyah, 2025)
The internalisation of constructivism theory in the learning process highlights the main problems that are still often encountered in the world of education, namely the tendency of PAI teachers to position students as passive recipients of knowledge and conventional ways of learning. This research uses the literature study method by examining various scientific sources related to constructivism theory and its implementation in learning. The results showed that constructivism in PAI places students as active subjects who construct knowledge through experience and interaction, while the teacher acts as a facilitator who guides the critical and reflective thinking process. This approach has advantages in encouraging independence, creativity, and deeper understanding in students, but also faces challenges in the form of time requirements, teacher readiness, and limited resources in large classes. This research confirms the importance of applying constructivism to create meaningful learning that is relevant to learners' needs, while recommending the need for teacher training and adjustments to the learning environment so that this approach can be implemented optimally.